Discretionary Accruals under Positive Accounting Theory: The Role of Sustainability Disclosure and Ownership Governance in Indonesian Basic and Chemical Industry Firms - Denny Putri Hapsari Putri; Denny Kurnia Denny (Yayasan Sinergi Kawula Muda, 2026)
This study examines signed discretionary accruals as accounting choice behavior within the Positive Accounting Theory (PAT) framework in Indonesian basic and chemical industry firms. Using balanced panel data from 58 firms during 2021–2024 (232 firm-year observations), discretionary accruals are measured using the Modified Jones Model, while the analysis employs a cross-section fixed effects model selected through Chow and Hausman tests. The findings provide partial and conditional support for PAT. Profitability shows a weak negative association with signed discretionary accruals, indicating limited support for the bonus-plan hypothesis. Leverage is negatively and significantly associated with signed discretionary accruals, suggesting that debt-contracting pressure encourages more income-decreasing or less income-increasing accrual choices. Firm size demonstrates the strongest negative association, indicating that political costs represent the most robust PAT mechanism in this sector. Sustainability disclosure significantly moderates the relationships between profitability, leverage, firm size, and signed discretionary accruals. Institutional ownership also moderates the profitability and leverage channels but does not influence the firm-size channel. In contrast, managerial ownership does not significantly moderate any of the tested relationships. Overall, the findings suggest that accounting choice behavior in Indonesian basic and chemical industry firms is better explained by a conditional PAT perspective, where political costs and sustainability disclosure are more influential than bonus-plan incentives, while ownership governance operates selectively through institutional ownership.